Explorations into a dynamic process-oriented soil science - Frink, Douglas S. (Boston, MA : Elsevier, 2011)
The paradigm and models of traditional soil science lack the ability to adequately address issues of soil dynamics, environmental integration, and change. Unexplainable research results obtained from traditional soil studies applied to non-traditional soil phenomena in physical geography, archaeology and ecology speak to the current need for soil science to move beyond description and classification and into a dynamic process-oriented soil science capable of providing explanations. Soils do not behave as static inert geologic detritus affected by climate, organisms, relief, and parent material.
Includes bibliographical references (p. [95]-117).
Keywords: Soil science; Soils